Mothers as sex educators to their adolescent daughters - De Vera, Kathleya Vita Napolitano; Malicdem, Eleanor Alzate (2007.)
This study determined the level of knowledge of mothers on sex education specifically on the areas of safe sex and sex-related risks. It also attempted to identify whether the mothers teach their adolescent daughters about sex-education. Purposive sampling was utilized in the selection of the respondents of the study, which included 47 mothers, 47 adolescent daughters. They were from the three public high schools in the towns of Pangasinan namely: Bugallon, Labrador and Lingayen. A semi-structured survey questionnaire was used for the data collection. Responses of the respondents were subjected to frequencies, percentage and mean. The findings of the study showed that mothers had enough knowledge on safe sex and sex-related skills to be able to teach their adolescent daughters. However, the mothers' knowledge on sex education was not taught to their adolescent daughters due to lack of time, feeling awkward and immaturity of the daughters. The study indicated also that adolescents had their information about sex education primarily from their Home Economics classes and the media such as television and reading materials.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Mothers and daughters -- Philippines; Sex instruction